Social experiences shape behavioral individuality and within-individual stability. (2nd April 2019) - Jäger, Heidi Y; Han, Chang S; Dingemanse, Niels J
Abstract : We test the social niche specialization hypothesis by examining behavioral individuality and within-individual stability in aggression and dietary preference. We used male field crickets raised alone or with conspecifics. We show that repeated social interactions lead to long-term individual differences in aggression. Living with a competitor decreased protein consumption but did not affect individual differentiation in dietary intake. Abstract: Individual repeatability characterizes many behaviors. Repeatable behavior may result from repeated social interactions among familiar group members, owing to adaptive social niche specialization. In the context of aggression, in species like field crickets, social niche specialization should also occur when individuals repeatedly interact with unfamiliar individuals. This would require the outcome of social interactions to have carry-over effects on fighting ability and aggressiveness in subsequent interactions, leading to long-term among-individual differentiation. To test this hypothesis, we randomly assigned freshly emerged adult males of the southern field cricket Gryllus bimaculatus to either a solitary or social treatment. In social treatment, males interacted with a same-sex partner but experienced a new partner every 3 days. After 3 weeks of treatment, we repeatedly subjected treated males to dyadic interactions to measure aggression. During this time, we also continuously measured the 3-daily rate of carbohydrate and protein consumption. Individual differentiation was considerably higher among males reared in the social versus solitary environment for aggressiveness but not for nutrient intake. Simultaneously, social experience led to lower within-individual stability (i.e., increased within-individual variance) in carbohydrate intake. Past social experiences, thus, shaped both behavioral individuality and stability. While previous research has emphasized behavioral individuality resulting from repeated interactions among familiar individuals, our study implies that behavioral individuality, in the context of aggression, may generally result from social interactions, whether with familiar or unfamiliar individuals. Our findings thus imply that social interactions may have a stronger effect on individual differentiation than previously appreciated.